Malformation risks of antiepileptic drug monotherapies in pregnancy: updated results from the UK and Ireland Epilepsy and Pregnancy Registers. Issue 9 (20th January 2014) - Campbell, E; Kennedy, F; Russell, A; Smithson, W H; Parsons, L; Morrison, P J; Liggan, B; Irwin, B; Delanty, N; Hunt, S J; Craig, J; Morrow, J
Abstract : Objectives: Antiepileptic drug (AED) exposure during pregnancy increases the risk of major congenital malformations (MCMs). The magnitude of this risk varies by AED exposure. Here we provide updated results from the UK Epilepsy and Pregnancy Register of the risk of MCMs after monotherapy exposure to valproate, carbamazepine and lamotrigine. Methods: Fifteen-year prospective observational study from 1996 until 2012. The main outcome measure is the MCM rate. Results: Informative outcomes were available for 5206 cases. 1290 women were exposed to valproate monotherapy, 1718 to carbamazepine monotherapy and 2198 to lamotrigine monotherapy. The MCM risk with valproate monotherapy exposure in utero was 6.7% (95% CI 5.5% to 8.3%) compared with 2.6% with carbamazepine (95% CI 1.9% to 3.5%) and 2.3% with lamotrigine (95% CI 1.8% to 3.1%). A significant dose effect was seen with valproate (p=0.0006) and carbamazepine (p=0.03) exposed pregnancies. A non-significant trend towards higher MCM rate with increasing dose was found with lamotrigine. MCM rate for high-dose lamotrigine (>400 mg daily) was lower than the MCM rate for pregnancies exposed to <600 mg daily of valproate, but this was not significant (3.4% vs 5.0%, p=0.31). Conclusions: In utero exposure to valproate carries a significantly higher MCM risk than lamotrigine (p=0.0001) and carbamazepine (p=0.0001) monotherapy. In contrast to prior findings, high-dose lamotrigine was associated with fewer MCMs than all doses of valproate. While lamotrigine has a favourable profile compared with valproate for adverse pregnancy outcomes, the requirements for seizure control should not be overlooked.